PEMIKIRAN FIKIH LINGKUNGAN YUSUF AL-QARAḌAWI (Sebuah Upaya Mewujudkan Maṣlaḥah al-’Ammah) (IAIN Tulungagung, 2019)
Being one of prominent figures in the field of fiqh, Yusuf al-Qaraḍawi is one of the contemporary scholars who initiates the ideas and thoughts about fiqh bīʻah (fiqh of environment). The current global environmental crisis ranging from global warming, climate changes, ozone layer depletion, acid rain, exploitation of natural resources, illegal logging, deforestation, floods, droughts, landslides, extinction of biodiversity, and so forth, have been becoming global crucial problems until now. These phenomena become a serious issue since they endanger and threaten the sustainability of the earth. This paper is aimed to study the Islamic perspective on safeguarding the nature and its contents in order to realize maṣlaḥah al-‘ammah (the public benefits) to the entire population of the earth. The thoughts of Yusuf al-Qaraḍawi need to be disseminated in order to realize the values of maṣlaḥah al-‘ammah so that the purpose of realizing Islam as the religion of raḥmatan li al-‘ālamīn (a blessing to all of the universe) may come true.Keywords: Fiqh Bīʻah, Jurisprudence of Environment, Maṣlaḥah al-‘Ammah, Public Benefits